Lifelong Learning as a Pathway: Strengthening Rural Communities for the SDGs - Prasetyo, Iis; Kusumawardani, Erma (Journal of Nonformal Education, 2025)
Background: The acceleration of globalization and the development of information and communication technology (ICT) have brought the world into an era of planetary urbanization, fraught with challenges such as climate change, financial crises, ecological degradation, and pandemics. In response, the United Nations (UN) formulated the 2030 Agenda for Sustainable Development Goals (SDGs). In Indonesia, the SDGs are integrated into village development through the Village Fund policy, as mandated by Law Number 6 of 2014. Urgency of Research: Although Village Funds have been proven to promote sustainable development, the implementation of the Village SDGs still faces various challenges, including low community participation, imbalances between physical development and human empowerment, and weak external stakeholder support. Previous studies have focused primarily on the use of Village Funds for infrastructure development, while their relationship to achieving Village SDG indicators has rarely been comprehensively examined. Research Objectives: This research aims to analyze the extent to which Village SDGs can be achieved through the utilization of Village Funds and to examine how a people-centered development approach through lifelong learning is a key strategy in realizing sustainable village development in Yogyakarta. Research Methods: This study employed a qualitative approach with exploratory methods. Data were obtained through in-depth interviews with village officials and field observations in 5 villages in the Special Region of Yogyakarta Province, selected using purposive sampling based on geographic location and potential. Data analysis was conducted through data reduction, narrative presentation, and conclusion drawing, with validation through source and method triangulation. Research Findings: Research results indicate that lifelong learning plays a strategic role in strengthening the social, economic, and environmental capacity of village communities. Findings in Bangunharjo, Margoluwih, Bosot, Wedomartani, and Sidoluhur demonstrate that community-based skills training, environmental education, and health programs can foster critical awareness, economic independence, and women’s involvement. Furthermore, partnerships between actors (village government, PKK, youth organizations, farmer groups, and external stakeholders) create social capital that accelerates SDG implementation. However, obstacles remain, including budget constraints, low community participation, technical constraints, and the misalignment of external programs with village priorities. Conclusion and Novelty: The study concludes that lifelong learning is not only an educational strategy but also a framework for socio-economic transformation that strengthens human capital, expands capabilities, fosters critical awareness, and strengthens village social capital. The novelty of this research lies in the empirical analysis linking the use of Village Funds to the achievement of Village SDGs indicators through the perspective of lifelong learning and people-centered development, a previously unstudied approach in the Indonesian context.